Algunas Consideraciones sobre el arte maya - Rivera Dorado, Miguel (Revista Española de Antropología Americana, 2001)
Although there are tens of publications in the bookshops about prehistoric mayan art, there are not so many cases in which authors decide to go beyond the descriptive aspects and insist on formal or stylistic criteria which is more proper to the History of Art in general and better favours the comparative points of view. We will try to demonstrate in this article some of the criteria by which we think that mayan art acquires its singularity.